2013
DOI: 10.1017/s0317167100016024
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Saline Attenuated Neuropathic Pain by Reducing Oxidative Stress

Abstract: Reactive oxygen species (RoS) are involved in the development of pains in various conditions, including neuropathic and inflammatory pain [1][2][3][4][5] . Park et al reported increased RoS in the spinal cord of rats after peripheral nerve injury 6 . others found that treatment with RoS scavengers phenyl Ntert-butylnitrone (PbN), 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl (tEMPoL), 5,5-dimethylpyrroline -N-oxide (DMPo) or vitamin E could temporarily reverse the allodynia developed after nerve ligation in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
4
9
0
Order By: Relevance
“…Recently, it was reported that intrathecal administration of hydrogen-rich saline relieve neuropathic pain induced by CCI in rats [22]. This accord with our study and further support the possibility of therapeutic use of hydrogen in pain medicine.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it was reported that intrathecal administration of hydrogen-rich saline relieve neuropathic pain induced by CCI in rats [22]. This accord with our study and further support the possibility of therapeutic use of hydrogen in pain medicine.…”
Section: Discussionsupporting
confidence: 92%
“…Growing research and our previous studies have also shown the protective and preventive effects of H 2 in sepsis, MODS, LPS-induced acute lung injury, neuropathic pain, etc., without remarkable side effects, by reducing inflammation response, apoptosis, and oxidative stress [13][14][15][16][17][18]. In this study, neuropathic pain was induced by chronic constriction of sciatic nerve, which contributed to the development of both hyperalgesia and allodynia.…”
Section: Discussionmentioning
confidence: 84%
“…Hydrogen has been reported to play a vital therapeutic role in sepsis, multiple organ dysfunction syndrome (MODS), lipopolysaccharide (LPS)-induced acute lung injury (ALI), and chronic pain, among others, through its anti-apoptosis effect, alleviating excessive inflammatory response and oxidative stress [13][14][15][16][17][18]. This strongly implies that hydrogen (H 2 ) treatment has beneficial and anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“… 33 Besides, HRS could improve the mechanical threshold of neuropathic pain in a rat model of chronic constriction injury, which possibly by reducing oxidative stress and the subsequent expression of p38 MAPK and brain-derived neurotropic factor. 34 In a controlled cortical impact model, HRW totally blocked the elevations of phosphorylated tau both in hippocampal and cortical regions, thus protected against neurodegenerative changes. 35 Moreover, it has been further clarified that HRW treatment decreased pro-inflammatory cytokine levels and increased anti-inflammatory cytokine levels using the same model.…”
Section: T He R Esearch P mentioning
confidence: 95%